Blockholder dispersion and firm value - Sander J. J. Konijn; Roman Kräussl; André Lucas (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
This paper analyzes the impact of blockownership dispersion on firm value. Blockholdings by multiple blockholders is a widespread phenomenon in the U.S. market. It is not clear, however, whether dispersion among blockholder is preferable to having a more concentrated ownership structure. To test for the direction of the effect, we use a large dataset of U.S. firms that combines blockholder information, shareholder rights information, debt ratings, accounting information, and financial markets information. We find that a large fraction of aggregated block ownership negatively affects Tobin's Q. The negative impact is larger if blockowners are more dispersed, suggesting that a concentrated ownership structure is to be preferred on average. Results are robust to controlling for blockholder type as well as proxies for shareholder rights. Our empirical findings are also confirmed if we study the impact of ownership dispersion on firm debt ratings rather than Tobin's Q.
urn:nbn:de:hebis:30-75241
Keywords: G12; 330; Corporate Governance; Ownership Structure; Multiple Blockholders; Firm Value; Corporate Governance; Eigentümerstruktur; Unternehmenswert; Tobin's Q; Schätzung; USA